Legal regulation of labor relations in Russia in the context of digitalization - Chucha, Sergey (Bulletin of Yerevan University C: Jurisprudence, 2022)
The article deals with the actual problems of the transformation of the sphere of labor in Russia in the context of the modernization of the organization of production, the digitalization of the economy and public life. The latest legislation on electronic personnel document management, remote (remote) work and the use of artificial intelligence, as well as the practice of their application in labor relations, is being studied. The prospects for the legal regulation of the sphere of labor are determined, related to the fixing in the labor legislation of the norm on the "silence mode" in labor relations; the spread of legal regulation of remote work to all categories of the precariat, as well as to all cases of the use of labor not under an employment contract (self-employed, working under an agreement with aggregators, individual entrepreneurs who do not use hired labor, etc.); the widespread introduction of blockchain and digital cloud as technologies that provide the greatest security in the transfer and storage of data; the introduction of elements of artificial intelligence in labor relations.